Analysis of the Principal's Role in Improving the Quality of Primary School Management - Kadariah, Kadariah (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
This study aims to: (1) describe the principal’s strategies to plan, organize, actuate, and control the school programs to improve the quality of education at SMP 1 Cilawu; and (2) describe constraints in  the  improvement  of  the  quality  of  education.  This  was  a  case  study  with  qualitative  approach.  The research  subjects  included  teachers  and  educational  personnel.  The  results  of  the  study  used  the principal’s as a manager: (1) plans programs by specifying the needs for teachers and educational personnel who will carry out duties, programs in the form of policies and the curriculum that will be implemented, and policies to add the time slot for the guidance and counseling subject by two hours a week; (2)  makes  an organizational  structure  by  involving students’parents  through  the  school committee and completing infrastructure facilities that the school needs; (3) gives examples of how to work  well  and  calmly,  motivation,  and  rewards  to  the  personnel  morally  and  materially,  improves welfare, sends teachers and educational personnel to trainings, and motivates senior teachers to have  spirit of lifelong education; and (4) controls the output, teaching and learning processes, and students from  the  enrolment  to  the  graduation.  (5)  The  constraints  include  the  facts  that  there  are  personnel who  are  not  disciplined,  there  is  a  lack  of  communication  between  the  principal  and  some  of  the personnel, and the school operation aid funds do not match the school’s needs..